Concurrent epidermal growth factor receptor mutation and anaplastic lymphoma kinase translocation in non-small cell lung carcinoma: A therapeutic conundrum (Indian Journal of Case Reports, 2025)
In non-small cell lung cancer (NSCLC), two key genetic alterations, epidermal growth factor receptor (EGFR) mutations, and echinoderm microtubule-associated protein-like 4-anaplastic lymphoma kinase (ALK) rearrangements are commonly believed to be mutually exclusive. Studies have reported that concurrent EGFR/ALK co-mutation in NSCLC patients is rare, with a prevalence ranging from 0.1% to 1.6%. In this case report, we present the case of a 49-year-old female with stage IV lung adenocarcinoma with both EGFR mutation and ALK rearrangement. The patient received treatment with EGFR tyrosine kinase inhibitors, but the disease progressed and the patient succumbed to her disease. Our report also provides a comprehensive summary of the clinical and pathological features, as well as treatment strategies, for NSCLC patients with concurrent EGFR mutation and ALK rearrangement.